Training and research programmes in health risk assessment in Vietnam - Phuc Pham Duc; Tran Thi Tuyet Hanh; Hung Nguyen-Viet (2013)
Risk assessment is one of the three important components of the risk analysis framework. Risk assessment is the scientific method used to assess the level of a specific risk, from which different measures to control the risk is developed. In developed countries, risk assessment has been applied with sufficient guidelines and used in policy development. However, in developing countries, including Vietnam, the role of risk assessment in environmental health is still limited and not well applied in policy development, as the quantity and quality of studies on risk assessment is incomplete and not comprehensive. This paper reviews the current training, research programmes and policies on environmental health risk assessment in Vietnam. The authors also present possible solutions that could be applied in a comprehensive environmental health risk assessment in Vietnam. The results of the environmental health risk assessment should be tied with policy development to prevent diseases and to promote public health.